SMART SYSTEM KANDANG BIBIT AYAM PEDAGING MENGGUNAKAN ARDUINO MEGA 2560 R3 BERBASIS IOT - Nur Fajri, Muhammad; Rasyad, Sabilal; Abdurrahman (JURNAL TELISKA, 2023)
Controlling temperature, humidity, and providing proper feed and drink in broiler broiler cages are important factors in maintaining the health and growth of chickens. To improve the efficiency and quality of this control, a system was created that automatically regulates temperature, humidity, as well as feed and drink using the fuzzy method. The fuzzy method is used to process temperature and humidity sensor data and apply fuzzy logic decisions in controlling the intensity of heating lamps, fans, and feed and drink. Sensor data will be entered into a fuzzy system that has been developed, where linguistic variables such as "cold", "warm", and "dryâ€ will be used to represent temperature and humidity conditions. Through the interface provided, breeders can monitor and adjust temperature settings, humidity, and feeding and drinking schedules automatically. This interface allows breeders to enter preferences and limits in the fuzzy system, as well as see a visualization of the conditions of the cage and the decisions produced by the system. By implementing this smart broiler cage system with the fuzzy method, it is hoped that farmers can improve the efficiency of temperature and humidity control, as well as improve the quality of feeding and drinking. This will contribute to better growth and optimal health for broiler breeders, as well as increase productivity and profitability in broiler farms.